1994
DOI: 10.1111/j.1539-6924.1994.tb00080.x
|View full text |Cite
|
Sign up to set email alerts
|

A Psychological Study of the Inverse Relationship Between Perceived Risk and Perceived Benefit

Abstract: Judgments of risk and judgments of benefit have been found to be inversely related. Activities or technologies that are judged high in risk tend to be judged low in benefit, and vice versa. In the present study, we examine this inverse relationship in detail, using two measures of relationship between risk and benefit. We find that the inverse relationship is robust and indicative of a confounding of risk and benefit in people's minds. This confounding is linked to a person's overall evaluation of an activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

49
546
6
7

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 914 publications
(608 citation statements)
references
References 16 publications
49
546
6
7
Order By: Relevance
“…Likewise, Nisbett and Ross (1980) argue that vivid, concrete information has a greater influence on perceptions and inferences than 'pallid' (e.g., abstract and technical) information. Among other findings, this research has identified an 'affect heuristic' -an orienting mechanism that allows people to navigate quickly and efficiently through a complex, uncertain and sometimes dangerous world, by drawing on positive and negative feelings associated with particular risks (Alhakami and Slovic, 1994;Finucane et al, 2000). This research trajectory has also developed affective image analysis -a structured form of word association and content analysis -as an invaluable method to investigate the relationship between affect, imagery and perceived risk (e.g., Benthin et al, 1995;Jenkins-Smith, 2001;Leiserowitz, 2005;Satterfield, 2001;Slovic et al, 1991).…”
Section: Experiential Vs Analytic Processing Of Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, Nisbett and Ross (1980) argue that vivid, concrete information has a greater influence on perceptions and inferences than 'pallid' (e.g., abstract and technical) information. Among other findings, this research has identified an 'affect heuristic' -an orienting mechanism that allows people to navigate quickly and efficiently through a complex, uncertain and sometimes dangerous world, by drawing on positive and negative feelings associated with particular risks (Alhakami and Slovic, 1994;Finucane et al, 2000). This research trajectory has also developed affective image analysis -a structured form of word association and content analysis -as an invaluable method to investigate the relationship between affect, imagery and perceived risk (e.g., Benthin et al, 1995;Jenkins-Smith, 2001;Leiserowitz, 2005;Satterfield, 2001;Slovic et al, 1991).…”
Section: Experiential Vs Analytic Processing Of Riskmentioning
confidence: 99%
“…Affect and feelings are not mere epiphenomena, but often arise prior to cognition and play a crucial role in subsequent rational thought. A large and growing literature has since emerged in several fields providing convergent lines of evidence for the critical role of affect in risk perception and decision making (Alhakami and Slovic, 1994;Damasio, 1994Damasio, , 1999Epstein, 1994;Lowenstein, 1996;Lowenstein et al, 2001;Peters and Slovic, 1996;Slovic et al, 1991. This literature is part of broader empirical and theoretical developments distinguishing "two parallel, interacting modes of information processing: a rational system and an emotionally driven experiential system" (Epstein, 1994, p. 709).…”
Section: Experiential Vs Analytic Processing Of Riskmentioning
confidence: 99%
“…The level of importance to the individual will also influence cognitive processes, with issue importance part of what has been termed 'attitude strength' (Pomerantz et al 1995). Studies of the affect heuristic, for instance, have shown that stronger attitude strength can increase biased information processing (c.f: Alhakami and Slovic 1994;Brannon et al 2007). Cognitive dissonance theory similarly has illustrated a range of mechanisms used to avoid, dismiss, or ignore cases where values are inconsistent, and stronger value violations would be anticipated when evidence is brought to bear on highly contested debates.…”
Section: Contestationmentioning
confidence: 99%
“…Alhakami and Slovic (1994), and Finucane et al (2000) found that risk and benefit are negatively related in peoples' minds even though they are positively correlated in the environment. They argue that the reason for this is that an affective feeling is referred to when the risks and benefits of specific hazards are judged.…”
Section: Inverse Relationship Between Perceived Risk and Perceived Bementioning
confidence: 99%